Department of Pastry Arts TOT: dramatic Opera, Charlotte and Entremet part 1 / Anida Ismail … [et al.] - Ismail, Anida; Mohamed Apandi, Siti Rohimi; Rozekhi, Nor Azureen; Yildirim, Nur Syazana (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
A quote by Mary Catherine Bateson once famously said "we are not what we know but what we are willing to learn." This is especially true for educators who seek self-improvement and knowledge betterment. Hence, in the spirit of lifelong learning, the Department of Pastry Arts has organized a Training of Trainers (TOT) course on July 29, 2024. The three-day training included the preparation of five topics or products: Entremet, Opera cake, Carrot cake, Charlotte, and dessert plating. We invited Chef Mohd Syafie bin Ismail, who hails from UNISHAMS, Alor Setar, and has vast experience in pastry arts and diversified talents in preparing pastries, bread and viennoiserie, desserts, chocolate work, and sugar artistry.